Devolatilization Kinetics of Different Types of Bio-Coals Using Thermogravimetric Analysis - Asmaa A. El-Tawil; Hesham M. Ahmed; Lena Sundqvist Ökvist; Bo Björkman (Metals, 2019)
The interest of the steel industry in utilizing bio-coal (pre-treated biomass) as CO2-neutral carbon in iron-making is increasing due to the need to reduce fossil CO2 emission. In order to select a suitable bio-coal to be contained in agglomerates with iron oxide, the current study aims at investigating the thermal devolatilization of different bio-coals. A thermogravimetric analyzer (TGA) equipped with a quadrupole mass spectrometer (QMS) was used to monitor the weight loss and off-gases during non-isothermal tests with bio-coals having different contents of volatile matter. The samples were heated in an inert atmosphere to 1200 °C at three different heating rates: 5, 10, and 15 °C/min. H2, CO, and hydrocarbons that may contribute to the reduction of iron oxide if contained in the self-reducing composite were detected by QMS. To explore the devolatilization behavior for different materials, the thermogravimetric data were evaluated by using the Kissinger⁻ Akahira⁻Sonuse (KAS) iso-conversional model. The activation energy was determined as a function of the conversion degree. Bio-coals with both low and high volatile content could produce reducing gases that can contribute to the reduction of iron oxide in bio-agglomerates and hot metal quality in the sustained blast furnace process. However, bio-coals containing significant amounts of CaO and K2O enhanced the devolatilization and released the volatiles at lower temperature.